The Relevance of Individual Candidates on The Local Leaders Election (PILKADA) in Indonesian Democracy (Study on: Analysis of The Defeat of The Candidate Obon Tabroni-Bambang Sumaryono) - Ahmad Syahrul Fadhil; Veithzal Rivai Zainal; Aziz Hakim (Dinasti Publisher, 2023)
This study discussed the relevance of individual candidates in Indonesian democracy, which had regulated the requirements for candidates to advance in Pilkada through individuals. In the Pilkada of Bekasi, candidate of Obon Tabroni and Bambang Sumaryono accepted support from various elements of society, this was the background for the candidate Obon Tabroni and Bambang Sumaryono to advance as candidates in the Pilkada of Bekasi as individuals. NGOs and labor unions were a strong asset in Bekasi, considering that part of the area was an industrial area. Other than that, Obon Tabroni was also the Director of Serikat Pekerja Metal Indonesia (FSPMI) Bekasi. although they had sufficiently strong support, in fact this candidate lost in the regional elections. This was also the concern in this research. This research used the theory of democracy and local elections. This regulation was ratified by the Constitutional Court (MK) 2007, as well as in Constitution, Article 40 no. 10 in 2016 which regulated the requirements for candidates to advance through the independent. In Indonesia, the individual was less popular, considering that the regional head or presidential candidates mostly used political parties as a vehicle to win. The problems that was faced by individual candidates also still struggled around clichéd issues, namely financial and logistical limitations, the lack of second-class voter participation, as well as other problems that were also frequently encountered by candidate who run through the party. With the increasing number of candidates nominating individually and seeing the conditions put forward by the KPU, it seemed that the existence of these individual candidates needed to be appreciated. This could also be a benchmark, that there had been growing political awareness in our society. Even though the chances of winning the Pilkada through individual were still small.